Regulation of stem cell fate and function by using bioactive materials with nanoarchitectonics for regenerative medicine. Issue 1 (31st December 2022) - Hu, Wei; Shi, Jiaming; Lv, Wenyan; Jia, Xiaofang; Ariga, Katsuhiko
ABSTRACT: Nanoarchitectonics has emerged as a post-nanotechnology concept. As one of the applications of nanoarchitectonics, this review paper discusses the control of stem cell fate and function as an important issue. For hybrid nanoarchitectonics involving living cells, it is crucial to understand how biomaterials and their nanoarchitected structures regulate behaviours and fates of stem cells. In this review, biomaterials for the regulation of stem cell fate are firstly discussed. Besides multipotent differentiation, immunomodulation is an important biological function of mesenchymal stem cells (MSCs). MSCs can modulate immune cells to treat multiple immune- and inflammation-mediated diseases. The following sections summarize the recent advances of the regulation of the immunomodulatory functions of MSCs by biophysical signals. In the third part, we discussed how biomaterials direct the self-organization of pluripotent stem cells for organoid. Bioactive materials are constructed which mimic the biophysical cues of in vivo microenvironment such as elasticity, viscoelasticity, biodegradation, fluidity, topography, cell geometry, and etc. Stem cells interpret these biophysical cues by different cytoskeletal forces. The different cytoskeletal forces lead to substantial transcription and protein expression, which affect stem cell fate and function. Regulations of stem cells could not be utilized only for tissue repair and regenerative medicine but also potentially for production of advanced materials systems. Materials nanoarchitectonics with integration of stem cells and related biological substances would have high impacts in science and technology of advanced materials. Graphical Abstract: uf0001